2016
DOI: 10.1080/09638288.2016.1239769
|View full text |Cite
|
Sign up to set email alerts
|

The role of the physical environment in conversations between people who are communication vulnerable and health-care professionals: a scoping review

Abstract: Purpose: The role of the physical environment in communication between health-care professionals and persons with communication problems is a neglected area. This study provides an overview of factors in the physical environment that play a role in communication during conversations between people who are communication vulnerable and health-care professionals. Method: A scoping review was conducted using the methodological framework of Arksey and O'Malley. The PubMed, PsycINFO, CINAHL and Cochrane Library data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Professionals and clients agreed about the importance of preparing conversations and ensuring a suitable environment, which has also been emphasized in previous research . Our observations showed that environmental issues were taken into account, but the preparation mostly did not include the clients.…”
Section: Discussionsupporting
confidence: 79%
“…Professionals and clients agreed about the importance of preparing conversations and ensuring a suitable environment, which has also been emphasized in previous research . Our observations showed that environmental issues were taken into account, but the preparation mostly did not include the clients.…”
Section: Discussionsupporting
confidence: 79%
“…Even minor changes in physicians’ behaviour can influence patients’ ability to participate actively in decision-making and problem-solving 39. In addition, suitable lighting and a calm environment can have a positive impact on communication with vulnerable patients, so health professionals are urged to be aware of the physical environment 40. To improve these aspects of care, it is valuable to continually monitor care quality through patient experience surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Talking Mats could be compared with other AAC tools aiming at visualisation, such as graphic topic setters, communication boards, pictographic books or picture pointing boards. 51 Both quantitative research using validated observation lists and qualitative research focussing on the experiences of communication vulnerable people would provide valuable information on the effective elements of Talking Mats. Information is also needed about effective implementation strategies for using Talking Mats in daily life/practice for communication vulnerable people.…”
Section: Empirical Evidence Of Talking Matsmentioning
confidence: 99%